Is educational software a luxury or a necessity in speech therapy for children diagnosed with intellectual disability? - Elena Crișan (Journal of Education, Society & Multiculturalism)
Technology is often used today in the therapies of children with language disorders, especially during the COVID-19 pandemic. Studies show that artificial intelligence makes the work of therapists more efficient in the corrective-recovery process. Largely due to new technologies, the importance of skills and abilities – application, critical thinking, creativity, problem solving, communication, collaboration – is increasingly confirmed to the detriment of verbal information. The evolution of technological means not only requires the educational system to form the student's ability to use them, but, at the same time, makes available to all educational actors a set of resources, tools and teaching methods, indispensable today for the efficiency of training, in all areas transposed into educational disciplines. At the same time, the current knowledge society, governed by the emergence of information technologies, displays a new set of educational imperatives with which the school must permanently align its purposes. This information society determines the emergence of a new type of student, the digital native, the young person born into a technology-dominated environment, who has an inherent understanding of digital technologies, these being integrated into his life since childhood. Thus, this study aimed to investigate possible differences between the opinions of specialists regarding the integration of educational software in speech therapy according to their demographic characteristics. Our results highlighted differences in terms of gender, level of education of the specialists and the type of disorder suffered by the child they are working with. These results can be used in the development of mentoring programs for specialists in the field of special psychopedagogy to make their work more efficient or in the corrective-recovery approach.